Gliserolisis enzimatik CPO dengan lipase amobil untuk produksi diasil dan monoasil gliserol (Enzymatic glicerolysis of CPO using immobilized lipase for production of diacyl- and monoacyl glycerol) - TRI - PANJI; Firda DIMAWARNITA; Irma KRESNAWATY; Susy SAADAH; Tri AMININGSIH; Mira MIRANTI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2019)
CPO is one of the largest plantation commodities that has a lot of derrivative products, among others are DiAcyl Glycerol (DAG) and MonoAcyl Glycerol (MAG). These derivative products have much higher added value because these can serve as healthy oil that able to prevent fat accumulation in human body.The industry of the derivative products is not yet developed in Indonesia, among others are caused by underdeveloped technology of specific lipase enzyme for the production of DAG 1.3- glycerides, the stability and the activity of lipase enzyme need to be improved. This research was conducted with the aim to develop the production technology for 1.3-glycerides, developthe technology forlipase immobilization, develop the technology for CPO glycerolysis with immobilized lipase, and obtain the data composition of glycerolysis products. Lipase-producing fungi were isolated from tempeh, then cultured in a growth medium containing CPO. Lipase was then immobilized on severall solid support. Glycerolysis product composition was analyzed by Thin Layer Chromatography. The research results showed that the immobilization of lipases from Rhyzopus oryzae with adsorption techniques can be performed using zeolite, CaCO3, silica gel, and cow bones. The highest activity of immobilized lipase is on CaCO3as much as 99.46%, then on cow bones (91.56%), on zeolite (90.69%), andsilica gel (59.63%). The optimum condition of non immobillized lipase is pH 7 and temperature 30 °C, while immobilized lipase on CaCO3 is at pH 8 and temperature35 ° C. Lipase immobilized on zeolite is at pH 8 and temperature of 30 ° C, on cow bone is at pH 7 and temperature of 30° C, andon silica gel is at pH 8 and temperature of 30° C. The all immobilized lipases are more stable than the free enzyme since the first week of storage. The optimum time of DAG production by immobilized lipase on CaCO3 is 18 hours to produce DAG level of 34.49% of the substrate.[Keywords: enzymatic glycerolysis, lipase, DAG, MAG, enzyme immobilization] AbstrakCPO merupakan komoditas perkebunan yang memiliki banyak produk turunan, di antaranya Diasil Gliserol (DAG) dan Monoasil Gliserol(MAG). Produk turunan tersebut memiliki nilai jual yang tinggi karena dapat berfungsi sebagai minyak sehat dengan kemampuannya mencegah akumulasi lemak dalam tubuh. Industri produk turunan ini belum banyak berkembang di Indonesia karena belum berkembangnya teknologi produksienzim lipase spesifik 1,3 gliserida untuk produksi DAG, serta stabilitas dan aktivitas enzim lipase yang masih perlu ditingkatkan.Penelitian ini bertujuan untuk mengembangkan teknologi produksi lipase spesifik 1,3-gliserida, teknologi amobilisasi lipase, teknologi gliserolisis CPO dengan lipase amobil, dan memperoleh data komposisi produk gliserolisis. Fungi penghasil lipase diisolasi dari tempe atau oncom, kemudian dibiakkan dalam media tumbuh mengandung CPO. Lipase kemudian diamobilisasi dalam beebrapa padatan pendukung. Komposisi produk gliserolisis dianalisis dengan metode Kromatografi Lapis Tipis. Hasil penelitian menunjukkan bahwa amobilisasi enzim lipase Rhyzopus oryzaedengan teknik adsorpsi dapat dilakukan menggunakanzeolit, CaCO3, silika gel, dan tulang sapi. Aktivitas enzim tertinggi terdapat pada enzim yang diamobilisasi CaCO3sebesar 99,46%, kemudiantulang sapi 91,56%, zeolit 90,69%, dan silika gel 59,63%. Kondisi optimum lipase bebas ialah pH 7 dan temperatur 30 °C, sedangkan lipase teramobilpada CaCO3ialah pH 8temperatur 35 °C,lipase teramobil zeolit ialah pH 8 temperatur 30°C, lipase teramobil tulang sapi ialahpada pH 7 temperatur 30°C, dan lipase teramobilsilika gel ialah pH 8 temperatur 30 °C. Seluruh lipase teramobil lebih stabil dibandingkan enzim bebas sejak penyimpanan pada minggu pertama.Waktu optimum produksi DAG dengan lipase teramobil pada CaCO3ialah selama 18 jam menghasilkan kadar DAG sebesar 34,49% dan MAG 29,22% dari substratnya.[Kata kunci: gliserolisis enzimatik, lipase, DAG, MAG, amobilisasi enzim